2014
DOI: 10.1073/pnas.1314226111
|View full text |Cite
|
Sign up to set email alerts
|

The Fanconi anemia pathway has a dual function in Dickkopf-1 transcriptional repression

Abstract: Fanconi anemia (FA) is an inherited bone marrow failure syndrome associated with a progressive decline in hematopoietic stem cells, developmental defects, and predisposition to cancer. These various phenotypic features imply a role of FA proteins in molecular events regulating cellular homeostasis. Interestingly, we previously found that the Fanconi C protein (FANCC) interacts with the C-terminalbinding protein-1 (CtBP1) involved in transcriptional regulation. Here we report that FANCC with CtBP1 forms a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…For example, knockdown of FANCC, a member of the Fanconi anemia complex (Huard et al, 2014; Marathi et al, 1996), promoted HIV reactivation. Most of the 25 shRNAs for FANCC were relatively enriched in the double-positive population (i.e., FANCC is latency-promoting) (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…For example, knockdown of FANCC, a member of the Fanconi anemia complex (Huard et al, 2014; Marathi et al, 1996), promoted HIV reactivation. Most of the 25 shRNAs for FANCC were relatively enriched in the double-positive population (i.e., FANCC is latency-promoting) (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The upper band (slightly larger form) is monoubiquitinated FANCD2 (FANCD2-L), and the lower band is unubiquitinated FANCD2 (FANCD2-S) (40, 41). The ratio of FANCD2-L to FANCD2-S (L/S) was calculated by densitometry.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, we also observed a significant enrichment of genes involved in Wnt signaling (Figure 3A). We decided to evaluate this pathway, as previous studies have suggested a possible interaction of Fancc with Wnt signaling (15, 16) and the involvement of Wnt signaling in B cell development (28, 29). Up-regulation and down-regulation of both inhibitors (Camk2b, Ankrd6, Sfrp1, Axin2, Nkd1, Tax1bp3) and activators (Dlg2, Fhl2) of the Wnt pathway and deregulated expression of Wnt receptor genes (Fzd-9, 2 and 4) were detected in Fancc −/− B cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, two recent studies have shown that FANCC is able to interact with Ctbp1 and β-catenin and regulates the expression of the Wnt inhibitor Dkk1 and that the integrity of the FA core complex is indispensable for a normal Wnt activity (15, 16). We observed no alteration in Dkk1 expression in our transcriptome analysis but found deregulation of several genes implicated in the Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation